Association between Postoperative Thrombocytopenia and Acute Kidney Injury in On-Pump versus Off-Pump Coronary Artery Bypass Grafting - Rehman, Atiq ur; Sobia, Farah; Janjua, Asif Mahmood; Paracha, Vaqar Illahi; Noor, Mudassar Noor; Akhtar, Muhammad Usama (Pakistan Armed Forces Medical Journal, 2026)
Objective: To assess the association between postoperative Thrombocytopenia and Acute Kidney Injury (AKI), in patients undergoing on-pump and off-pump coronary artery bypass grafting (CABG). Study Design: Quasi Experimental Study. Place and Duration of Study: Department of Cardiac Surgery, Armed Forces Institute of Cardiology/National Institute of Heart Diseases (AFIC/NIHD), Rawalpindi Pakistan, from Aug 2025 to Jan 2026. Methodology: The study evaluated 136 patients over the age of 18, regardless of gender, who underwent isolated CABG with left ventricular function (LVEF >35%) and coronary artery disease (CAD) of single, double, or triple vessels. Patients were excluded if they had bleeding disorders, baseline hepatic or renal dysfunction. Patients with concomitant CABG and valvular surgery were also excluded. Platelet counts and serum creatinine were measured postoperatively at 12, 24, and 48 hours, and at discharge. Results: Baseline platelet counts were almost similar between both groups. Postoperatively, Off-Pump patients experienced less reduction in platelet count compared to On-Pump and recovered by discharge (222.23±75.78 vs. 178.02±54.36, p-value =0.001) and had less creatinine increase (1.14±0.48 mg/dL vs. 1.29±0.44 mg/dL, p-value =0.05) from baseline. The frequency of AKI was somewhat higher in the On-pump CABG group (26.0% vs. 20.0%), and in both groups, AKI was not significantly associated with postoperative thrombocytopenia (p-value >0.05). Conclusion: Off-pump CABG is associated with milder platelet decline and reduced renal stress compared to on-pump CABG, suggesting that CPB contributes to increased postoperative morbidity, though thrombocytopenia did not significantly influence AKI .